Damn! : a cultural history of swearing in modern America - Chirico, Rob (Pitchstone Publishing, 2014)
Swearing, cussing, or cursing, out of anger, excitement, or just because, is something most of us do, at least to some degree. Turn on the television or open a magazine, and there it is. Damn! is an insightful and entertaining look at our evolving use of profanity over the last half-century or so, from a time when Gone with the Wind came under fire for using the word "damn" to an age where the f-bomb is dropped in all walks of life. Writer and artist Rob Chirico follows the course of swearing through literature, the media, and music, as well as through our daily lives. From back rooms and barracks to bookshelves and Broadway; and from precedents to presidents, the journey includes such diverse notables as George Carlin, the Simpsons, D.H. Lawrence, Ice T, Barack Obama, Nietzsche, and, of course, Lenny Bruce. If you have ever stopped and wondered WTF has happened to our American tongue, don't get out the bar of soap until you finish Damn!